EFFECT OF COMBINATION PURSED LIP BREATHING AND GUIDED IMAGERY MUSIC ON PEAK EXPIRATORY FLOW PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Hariyono, Rudi; Soedarsono, Soedarsono; Makhfudli, Makhfudli (Jurnal Keperawatan, 2019)
ABSTRACTBackground: Peak expiratory flow influenced by several things, such as anxiety, a psychological factor that is becoming a major comorbidities of COPD and affect the occurrence of exacerbations, increase respiration rate, duration expiratory time, and hyperinflation. This study aimed to determine the effect of combination pursed lip breathing and guided imagery music to increaseÂ  value of peak expiratory flow in patients with COPD. Methods: The study was quasi-experimental design with pretest posttest with control group approach, respondents of this study is 46 patients with COPD with sampling technique, simple random sampling. Results: Pursed lip breathing increase peak expiratory flow values by the significant of p value = 0.000 (p <0.05). The combination of pursed lip breathing and guided imagery music increase peak expiratory flow values by the significant of p value = 0.000 (p <0.05). COPD patients who received a combination of pursed lip breathing and guided imagery music increased peak expiratory flow value higher than the pursed lip breathing without combination with significant of p value = 0.000 (p <0.05).Conclusion:The combination of pursed lip breathing and guided imagery music proved to have an effect on increasing the value of peak expiratory flow higher than pursed lip breathing without combination.